On the Legal Issues of the Protection of Consumer Rights and Interests in E-commerce - Bo Zhao, Xin Su, Yuheng Fan (Law and Economy, 2022)
With the rapid development of e-commerce, consumers are becoming more and more used to online shopping. In transactions, consumers are easy to be deceived by false publicity, and personal information is easy to divulge, so we should further explore the protection of consumer rights and interests in the legislative field of e-commerce law.